Synthesis And Characterization Of Methyl 4, 6-O-Enzylidene- ?-D-Glucopyranoside Derivatives - Kawsar, Sarkar MA; Kabir, Abul KMS; Bhuiyan, MOhammad MR; Manik, Mohammad M (Journal of the Bangladesh Chemical Society, 2013)
Regioselective benzoylation of methyl 4,6-O-benzylidene-?-D-glucopyranoside (1) using direct acylation method furnished the methyl 4,6-O-benzylidene-2-O-(4-t-butylbenzoyl)- ?-D-glucopyranoside (2) in an excellent yield. In order to obtain newer products for antimicrobial screening studies, the 2-O-4-t-butylbenzoyl derivative was further transformed to a series of 3-O-acyl derivatives (2-12) containing a wide variety of functionalities in a single molecular framework. Journal of Bangladesh Chemical Society, Vol. 25(2), 101-109, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15045